Research on Risk in Global Production Networks—New Methodological Directions - Verfürth, Philip; Neise, Thomas; Völlers, Philip; Franz, Martin (DIE ERDE – Journal of the Geographical Society of Berlin, 2025)
Risk has become almost ubiquitous in today’s global economy and has developed into an emerging topic of global production networks (GPN) research. Recent conceptual contributions emphasize that risks are socially constructed and can gradually convert into a performative risk narrative (PRN) in global production networks. To explore how PRNs can be empirically analyzed, this article aims to outline new methodological directions to risk-related GPN research. Against this background, we discuss two methods: discourse analysis and vignette studies. Hence, we argue for research designs open to qualitative and quantitative methods, to gather the diversity of risk expectations and related actor-specific strategic reactions. With this contribution, we seek to stimulate a critical debate on the methodological reorientation of risk-related GPN research.